THE ATTITUDE TOWARDS NATIVE AMERICANS IN “THE LAST OF THE MOHICANS” BY J. F. COOPER - Yoriyeva Maftuna Umedovna; Qurbonova Nodira Roziqovna (Journal Park Publishing, 2023)
This article, explores the attitude of white English people towards native Americans in “The last of the Mohicans” by James Fenimore Cooper by means of samples, like the authors idea of native people of North America together with the ideas and attitude of the characters of the novel through presenting dialogues between the heros.
Keywords: Native Americans, Indians, an Indian runner, the scout, Hewkeye, alice, Cora, represent.